Changing clinical and molecular characteristics of hepatitis E virus infection in Mie Prefecture, Japan: Disappearance of indigenous subtype 3e strains. Issue 9 (7th June 2019) - Nakano, Tatsunori; Okano, Hiroshi; Takahashi, Masaharu; Nagashima, Shigeo; Shiraki, Katsuya; Oya, Yumi; Inoue, Hidekazu; Ohmori, Shigeru; Tsukimoto, Mone; Ishida, Satoshi; Fujimoto, Shino; Kobayashi, Makoto; et al.
Abstract : Aim: To evaluate the clinical and molecular characteristics of hepatitis E virus (HEV) infection in Mie Prefecture, Japan, from 2004 through 2018. Methods: The clinical information of hepatitis E cases was collected from 21 medical institutions in Mie Prefecture. The nucleotide sequences of infecting HEV strains were determined for cases with available serum samples. The origins or transmission routes were inferred from phylogenetic analyses of the nucleotide sequences. Results: Fifty‐three patients were diagnosed with HEV infection. The number of cases increased each year through 2012 and then decreased. Analyses of the clinical characteristics of the cases indicated that even mild cases were detected in the latter 10 years of the study. Nucleotide sequence analyses were undertaken on 38 of the 53 cases. The HEV subtype 3e (HEV‐3e) strains identified for 13 cases were closely related to a swine HEV‐3e strain that was isolated from the liver of a pig bred in Mie Prefecture. The number of cases infected with the indigenous Mie HEV‐3e strains increased until 2012 but have not been reported since 2014. In the latter half of the study, cases involving various HEV strains of different genotypes and subtypes emerged. Conclusions: The disappearance of indigenous Mie HEV‐3e strains appeared to be the primary cause for the decrease in hepatitis E cases in Mie Prefecture. The disappearance might have been associated with improved hygienic conditions on pig farms or the closure of contaminated farms. The results suggest that indigenous HEV strains can be eradicated by appropriate management.